Formulasi Tepung Jagung (Zea mays L.) dengan Tepung Kacang Hijau Terhadap Karakteristik Fisikokimia dan Organoleptik Flakes - Nabilatasya Maya Titonia; Suko Priyono; Lucky Hartanti (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2025)
One of the practical foods that can fulfill nutritional needs is flakes. Flakes that available on the market are generally made from wheat and corn. The nutritional value of corn flour-based flakes can be enhanced by combining them with other ingredients that have a relatively high protein content. One such food ingredient with a high protein content is mung beans. The development of flakes products using mung bean flour is expected to be one of the way to optimize the use of local legumes in Indonesia. The aim of this study is to obtain the best formulation of corn flour and mung bean flour in terms of the physicochemical and organoleptic characteristics of the flakes. This study uses a randomized block design with 4 treatment levels, which are the formulation ratios of corn flour to mung bean flour (60:40, 65:35, 70:30, 75:25), with each treatment repeated 6 times. The observation parameters include physicochemical characteristics such as protein, water and ash content, while sensory characteristics include aroma, taste, crispiness, color, and overall preference. The best treatment is determined by the de Garmo effectiveness index. The results of the study show that the 65% corn flour and 35% mung bean flour formulation is the best treatment based on the effectiveness index test with a score of 0.77, with physicochemical characteristics of 2.717% moisture content, 3.026% ash content, and 6.891% protein content, as well as sensory characteristics of color 4.2 (more liked), aroma 3.93 (liked), crispiness 4.26 (more liked), taste 4.23 (more liked), and overall preference 4.2 (more liked).